Climate change not to blame for late Quaternary megafauna extinctions in Australia - Frédérik Saltré (Nature Portfolio, 2016)
Global megafaunal extinctions took place in the late Quaternary, yet the relative impact of climate and humans in the faunal collapse is unclear. Here, the authors show that megafaunal extinctions in Australia were independent of climate variability and took place approximately 13,500 years after human arrival.